Effect of Eucalyptus Leaves Supplementation in Ration on Lactating Buffaloes Performance - Said Ahmed Mahmoud; Nabil Mohamed Eweedah; Hamed Mohamed Gaafar; Mostafa Mohamed El-Nahrawy; Sherif Ibrahim Al-Ajawi (ANIMAL PRODUCTION, 2021)
The present study was carried out to investigate the effect of fresh and dry eucalyptus leaves on feed intake, digestibility, rumen fermentation activity, blood serum biochemical, milk yield and composition, feed conversion and economic efficiency of lactating buffaloes. Twenty lactating multiparous Egyptian buffaloes in 3rd and 5th lactation seasons and weighed 550 kg on average were used in complete randomized design after 8 weeks of calving (peak period) and assigned into five similar groups of four buffaloes each according to milk yield and live body weight. Animals were individually fed on a basal ration (BR) consisted of 40% concentrate feed mixture (CFM), 30% fresh berseem (FB) and 30% rice straw (RS). The first group was un supplemented and served as a control group (G1). Those in the second and third groups were supplemented with 50 and 100 g of fresh eucalyptus leaves per head per day for low level (G2) and high level (G3). Animals in the fourth and fifth groups were supplemented with 15 and 30 g of dry eucalyptus leaves per head per day for low level (G4) and high level (G5). G3 recorded significantly the highest digestibility coefficients of all nutrients and feeding values followed by G2, G5 and G4, whereas control one (G1) had the lowest values. Ruminal pH value tended to decreased with Eucalyptus leaves additive. Group 3 showed significantly the highest TVFA’s and the lowest NH3-N concentration followed by G2, G5 and G4, while G1 had the opposite trend. Moreover, G3 revealed significantly the highest concentrations of total protein and globulin and the lowest urea, urea-N and creatinine and activity of SGOT and SGPT enzymes in blood serum followed by G2, G5 and G4, while G1 had reverse values. However, serum albumin concentration was nearly similar for the different groups. Group 3 recorded significantly the highest feed intake (DM, TDN and DCP), yield of actual milk and 7% FCM, milk composition (fat, protein, lactose, SNF, TS and ash) and milk constituents yield followed by G2, G5 and G4, while G1 had the lowest values. Also, G3 recorded significantly the lowest amounts of DM, TDN and DCP per 1 kg 7% FCM followed by G2, G5 and G4, while G1 had the highest amounts. At the same time, G3 recorded significantly the highest values of feed cost, output of 7% FCM yield, net revenue and economic efficiency and the lowest feed cost per kg 7% FCM followed by G2, G5 and G4, while G1 had the opposite values. In conclusion, addition of fresh eucalyptus leaves at the level of 100 g/head/day recorded the best improvements in feed intake, digestibility, rumen fermentation activity, some blood serum biochemical, milk yield and composition, feed conversion and economic efficiency of lactating buffaloes.